Hemodynamic responses to small muscle mass exercise in heart failure patients with reduced ejection fraction - Barrett-O'Keefe, Zachary (Am J Physiol Heart Circ Physiol, 2014)
To better understand the mechanisms responsible for exercise intolerance in heart failure with reduced ejection fraction (HFrEF), the present study sought to evaluate the hemodynamic responses to small muscle mass exercise in this cohort. In 25 HFrEF patients (64 ± 2 yr) and 17 healthy, age-matched control subjects (64 ± 2 yr), mean arterial pressure (MAP), cardiac output (CO), and limb blood flow were examined during graded static-intermittent handgrip (HG) and dynamic single-leg knee-extensor (KE) exercise. During HG exercise, MAP increased similarly between groups. CO increased significantly (+1.3 ± 0.3 l/min) in the control group, but it remained unchanged across workloads in HFrEF patients. At 15% maximum voluntary contraction (MVC), forearm blood flow was similar between groups, while HFrEF patients exhibited an attenuated increase at the two highest intensities compared with controls, with the greatest difference at the highest workload (352 ± 22 vs. 492 ± 48 ml/min, HFrEF vs. control, 45% MVC). During KE exercise, MAP and CO increased similarly across work rates between groups. However, HFrEF patients exhibited a diminished leg hyperemic response across all work rates, with the most substantial decrement at the highest intensity (1,842 ± 64 vs. 2,675 ± 81 ml/min; HFrEF vs. control, 15 W). Together, these findings indicate a marked attenuation in exercising limb perfusion attributable to impairments in peripheral vasodilatory capacity during both arm and leg exercise in patients with HFrEF, which likely plays a role in limiting exercise capacity in this patient population.